Analisis Peran Unit Reserse Kriminal Dalam Penanganan Tindak Pidana Umum Di Kepolisian Resor Kota Besar Palembang - Hendro, Hendro; Novaria, Eva; Sandy, Amiruddin (@-Publik: Jurnal Administrasi Publik, 2024)
The Criminal Investigation Unit (Reskrim) is an integral part of the police in handling general crimes. This research aims to analyze the role of the Criminal Investigation Unit in handling general crimes at the Palembang Police. The research method used is descriptive qualitative with data collection techniques through interviews and observation. The research results show that the Criminal Investigation Unit has a very important role in handling general criminal acts, starting from investigations, arrests, investigations, to prosecution. They work professionally and coordinate with other units in the police to achieve success in law enforcement. However, there are still several obstacles such as limited human resources and infrastructure that affect the performance of the Criminal Investigation Unit. Therefore, better efforts are needed in providing support to the Criminal Investigation Unit so that it can be more effective in handling general crimes at the Palembang Police.